Delirium Recognition by Family: European Portuguese Validation Study of the Family Confusion Assessment Method. Issue 9 (15th July 2014) - Martins, Sónia; Conceição, Filipe; Paiva, José A.; Simões, Mário R.; Fernandes, Lia
<x xml:space="preserve">Abstract</x> Objectives To present the validation study of the European Portuguese version of the Family Confusion Assessment Method (FAM‐CAM) and to assess the level of psychological distress in families and caregivers of elderly hospitalized adults with delirium. Design Validation study. Setting Intermediate care unit of the Intensive Medicine Service of the São João Hospital Center, Porto, Portugal. Participants Families and caregivers of elderly hospitalized adults (≥48 hours). Inclusion criteria were sufficient knowledge about the individual to enable reporting on his or her mental and physical abilities and staying at the individual's bedside daily during hospitalization. Families and caregivers younger than 18 and those who did not speak Portuguese were excluded. Measurements A trained researcher translated the FAM‐CAM according to International Society For Pharmacoeconomics and Outcomes Research guidelines. All individuals were assessed using the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision (DSM‐IV‐TR) (reference standard) and the Confusion Assessment Method (CAM). A trained researcher administered the FAM‐CAM to families and caregivers. The level of family‐perceived distress was evaluated on a numerical rating scale from 0 to 4. Results The sample included 40 families and caregivers (58% adult children). According to the DSM‐IV‐TR, 20% of individuals had delirium. The FAM‐CAM had moderate sensitivity (75%) and good specificity (91%) when assessed against the DSM‐IV‐TR and better sensitivity (86%) and specificity (91%) than the CAM. Fifty‐seven percent of families and caregivers classified delirium as an extremely distressing experience. Conclusion These preliminary results suggest that FAM‐CAM is a sensitive screening tool for family detection of delirium in elderly hospitalized adults. The high level of psychological distress found corroborated previous studies. Future studies with larger samples will be needed for further validation and to allow the analysis of other psychometric properties.